Pengaruh Penggunaan Model Pembelajaran Inkuiri terhadap Karakter Kreatif dan Karakter Kerja Keras di SMA - Astalini; Darmaji; Dwi Agus Kurniawan; Sabila Eka Septi; Rahmat Perdana (Postgraduate, University of Mataram, 2023)
Student creative character and student hard work character must be owned by students in order to form and strengthen their own personality, also help improve and train character education participants mentally and morally. the character of hard work students at the high school level. This type of research uses the miXII research method. The instrument in this study used the angle of students' creative character and student's hard work character. The results of the t-test obtained based on the table can be seen that there is a relationship between the variables of students' creative character and the character of students' hard work. The regression test results obtained based on the table can be seen that there is an effect of using inquiry learning model on the variables of students' creative character and students' hard work character.